The Conceptualisation of Diligence in Malay and Tamil Proverbs through the Hybrid Theory - Shanmugam, Parameswary; Sarudin, Anida; Husna Faredza Mohamed Redzwan; Zulkifli Osman (Issues in Language Studies, 2022)
This study aims to examine the conceptualisation of the diligence value in the Malay and Tamil proverbs based on the Hybrid Theory. This is a qualitative research design using the content analysis method. The research data are all of the proverbs denoting the value of diligence found in the Malay and Tamil textbooks used in the primary level but only four proverbs from these textbooks are part of the analysis. The analysis of the operational metaphor for each proverb is based on the domain features contained in the conceptual space defined in the Hybrid Theory. Additionally, the Malay and Tamil proverbs have its own moral values and philosophical foundations based on each context of the respective society. We suggest that the conceptual space visualises the similarities and differences in the comparison of the Malay and Tamil proverbs. The analysis displays a new approach in conceptualising proverbs according to the Malay and Tamil cultural thinking in tandem with the intellectual advancements of the respective tradition. Hence, this study of proverbs indirectly reveals a new perspective on the semantic-pragmatic aspects in Malay and Tamil civilizations for the readers.